The Quarantine Series Book - Folkersma, Nina; Quarantines Series, Amsterdam (Amsterdam : Quarantine Series Amsterdam, 2004)
Christensen, Jan; Declercq, Alain; Dejanov, Plamen; Hondius, Juul; Saethre, Borre; Yamaide Jun'ya.
Engels
Publicatie n.a.v. tentoonstelling "Open Office" in Quarantine Series te Amsterdam, 22.05.2004 - 27.06.2004
boek